Mucopolysaccharidosis I; Parental beliefs about the impact of disease on the quality of life of their children. Issue 1 (December 2016) - Soni-Jaiswal, A.; Mercer, J.; Jones, S.; Bruce, I.; Callery, P.
Abstract Background Hematopoietic stem cell transplants, alongside enzyme replacement therapy and good multi-disciplinary care, have dramatically improved the life expectancy in children with Mucopolysaccharidosis (MPS) I, with better objective and functional outcomes. Despite these improvements, children with both the attenuated (non-Hurler) and severe (Hurler) variants of the disease have marked residual morbidity. Children with MPS I suffer with head and neck disease including obstructive sleep apnoea and hearing loss. The impact of these on quality of life has been poorly researched and no previous work has been published looking at patients' perception of their own health, an important domain when considering the impact of treatment. Methods This exploratory qualitative study aimed to discover the effect of head and neck disease, alongside that of MPS I as a whole, on the quality of life of affected children. A grounded theory approach was used to conduct this study. Children and their parents were invited to participate in semi-structured interviews. The transcribed interviews were coded and emergent themes explored until saturation occurred. Results The families of eleven children with MPS I were interviewed, five with Hurler's and six with the attenuated non-Hurler's. Important themes to emerge were- the fear of dying associated with obstructive sleep apnoea, difficulties communicating at school due to the delayed acquisition of language, chronic pain and restricted mobility, physical differences and restricted participation in social activities such as sports secondary to the musculoskeletal disease burden. The overall theme running through the analysis was the desire to fit in with ones peers. Conclusion Parents and children with MPS 1 worry about 'fitting-in' with broader society. The presence of airway disease has a profound impact on the emotional well being of parents whilst language delay and musculoskeletal disease have the biggest impact on the quality of life of the children themselves. It is important to understand the impact of MPS I on the quality of life of children and their families so that we may improve future treatment and management of this sub-group of children who have an increasing life span.